Compostagem de resíduos sólidos urbanos no estado de São Paulo - Siqueira, Thais Menina Oliveira de (2014)
Are there successful composting experiences of municipal solid waste (MSW)? Is it possible to have alternative solutions for urban organic waste different from the conventional model of centralized composting plants? Answering these questions was the main objective of this work. The state of São Paulo was the focus of the research. Methodology included a survey of primary and secondary data of centralized and decentralized composting experiences in São Paulo and semi-structured interviews with managers in face to face, telephone or e-mail contacts. Six modalities of composting and fifteen treatment routes of organic waste with source separation had been identified, as well as factors boosting and restricting the development of composting activities in the State. The results showed the diversity of alternatives for organic waste recovery in urban areas, pointed out gaps that benefit final disposal groups and revealed the lack of public support to the composting activities undertaken by several actors in the State. The study concludes that decentralizing activities, diversifying technological routes of composting and stimulating social, public and private entrepreneurs can accelerate the diversion of MSW from landfills and dumps. Such actions can also contribute to urban and rural agriculture and enable implementation of a rational culture of solid waste management.